Hydrosols: Biological activity and potential as antimicrobials for food applications. (April 2018) - D'Amato, Serena; Serio, Annalisa; López, Clemencia Chaves; Paparella, Antonello
Abstract: The need for new antimicrobials to control microorganisms in foods has driven the research into natural products and, over the last few years, hydrosols have emerged as potential candidates. Hydrosols, or hydrolates, are secondary products of the hydrodistillation of plants; they consist of the distillation water in which very small amounts of essential oils remain dispersed. Historically used in traditional medicine in Mediterranean countries as refreshing drinks and flavorings, hydrosols have been recently noticed for their antimicrobial activity, both in vitro and in food matrices, particularly against pathogenic and spoilage microorganisms, including bacteria and fungi. Their antagonistic activity seems to be due to their chemical composition, being mainly constituted of phenolic compounds, which can interfere with microbial membranes, cell wall, or with the action of microbial enzymes. The use of hydrolates is already widespread in the cosmetic field, but the research carried out until now also suggests their application in the agro-food industry to hamper the development of pathogenic and spoiling microorganisms in food products and in working environments, and also in removing microbial biofilm. Moreover, their use could be exploited to counteract the phenomenon of antibiotic resistance. Hydrosols have been traditionally used also diluted in refreshing drinks, nevertheless toxycological implications should be better addressed. Highlights: Hydrosols are secondary products of hydro-distillation of plants. They exert antibacterial and antifungal activity in vitro and in situ. Different mechanisms of action related to their chemical composition are proposed. They could be applied in agro-food industry to improve safety and shelf-life. Hydrosols deserve deeper studies to assess application on foods and surfaces.